A new model to assess the environmental impact and sustainability of energy systems. (15th September 2015) - Hacatoglu, K.; Dincer, I.; Rosen, M.A.
Abstract: This study develops a novel sustainability assessment methodology for energy systems using life-cycle emission factors and sustainability indicators. Here, the global warming and environmental impact dimensions of the sustainability assessment methodology are examined in detail. A comparative analysis shows that a wind-battery system produces fewer potential global warming, stratospheric ozone depletion, air pollution, and water pollution impacts compared to a gas-fired system. The wind-battery system generates 13% of the life-cycle GHG emissions and 22% of the life-cycle ozone-depleting substance emissions of a gas-fired power plant. Nitrous oxide contributes more than 90% of the stratospheric ozone depletion potential of gas-fired and wind-battery systems. Highlights: We assess the environmental sustainability of a gas-fired power plant and wind-battery system. The wind-battery system has a lower environmental impact over its life cycle. Carbon emission reductions and higher standard of living with wind-battery system. Nitrous oxide is responsible for more than 90% of stratospheric ozone depletion.